Предмет: Математика,
автор: Аноним
2а+3b-(3b-2а)+2а-3b-(-3а-3b)-2+3b=
Ответы
Автор ответа:
1
2а+3b-(3b-2а)+2а-3b-(-3а-3b)-2+3b=2а+3b-3b+2a+2a-3b+(3a+3b)-2+3b=
=6a-6a-3b=-3b
=6a-6a-3b=-3b
Автор ответа:
1
2а+3b-(3b-2а)+2а-3b-(-3а-3b)-2+3b=
2а+3b-3b+2a+2a-3b+3a+3b-2+3b=
=6a-6a-3b
=-3b
2а+3b-3b+2a+2a-3b+3a+3b-2+3b=
=6a-6a-3b
=-3b
Похожие вопросы
Предмет: Математика,
автор: 1234567890779
Предмет: Математика,
автор: olganikitina33
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: seda0383mailrudani
Предмет: Математика,
автор: milana2457069595